2004
DOI: 10.1046/j.1600-0749.2003.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiotensin Converting Enzyme Gene I/D Polymorphism of Vitiligo in Korean Population

Abstract: Vitiligo (leukoderma) is an acquired idiopathic hypomelanotic disorder characterized by the circumscribed depigmented patches. Vitiligo is a polygenic disease. The exact pathogenesis is not yet known. The angiotensin converting enzyme (ACE) gene was selected as a candidate gene as ACE plays an important role in the physiology of the vasculature, blood pressure and inflammation, and its relationship with various diseases, including autoimmune diseases, has been widely investigated. The I/D polymorphism of ACE g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 18 publications
4
37
1
Order By: Relevance
“…Besides the association of vitiligo with CTLA‐4, vitiligo has been reported to be associated with several other genes (non‐HLA), such as the oestrogen receptor 1 gene, 46 the angiotensin‐converting enzyme gene, 47 the catalase gene, 48 the catechol‐ O ‐methyltransferase gene 49 and the lymphoid protein tyrosine phosphatase gene 50 . These observations, together with our findings in this study, provide evidence and support that the onset of vitiligo is complex and could be affected by multiple genes 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the association of vitiligo with CTLA‐4, vitiligo has been reported to be associated with several other genes (non‐HLA), such as the oestrogen receptor 1 gene, 46 the angiotensin‐converting enzyme gene, 47 the catalase gene, 48 the catechol‐ O ‐methyltransferase gene 49 and the lymphoid protein tyrosine phosphatase gene 50 . These observations, together with our findings in this study, provide evidence and support that the onset of vitiligo is complex and could be affected by multiple genes 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The genetic background underlying vitiligo susceptibility has been proposed in various studies (Spritz, 2006;Zhang et al, 2005). Several candidate genes have been proposed for vitiligo susceptibility, including catalase (CAT) gene (Casp et al, 2002;Park et al, 2006), angiotensin-converting enzyme (ACE) gene (Jin et al, 2004a), estrogen receptor 1 (ESR1) gene (Jin et al, 2004b) and cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) gene (Blomhoff et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we suggested that polymorphisms of angiotensin converting enzyme (ACE), oestrogen receptor 1 (ESR1) and catalase (CAT) contribute to the susceptibility to vitiligo in the Korean population (18–20). Casp et al (21) also reported that the CAT gene might be a susceptibility gene in Caucasian vitiligo patients.…”
Section: Discussionmentioning
confidence: 99%